Empowerment of Sto.Yohanes Maria Vianey Catholic Church Youth Naibonat of East Kupang, East Nusa Tenggara as A Supervision of Tuberculosis Ingestion - Novian A Yudhaswara; M Ibraar Ayatullah; Novelia G So o; Irwan Budiana; Norma Tiku Kambuno (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
Tuberculosis (TB) is an infectious disease that causes death, and is the third leading cause of death in Indonesia. The increase in cases of tuberculosis infection is still a major health problem in Naibonat Village, Kupang Regency, East Nusa Tenggara Province. Treatment failure, among others, was caused by patient non-compliance in ingesting drugs. It is hoped that the presence of supervisors to swallow drugs for TB patients is expected to help reduce TB infection cases. In Indonesian, a person who supervisors to swallow drugs is called “PMO” or “Pengawas menelan obat (PMO)” . Church Youth is an educated / educated group that is expected to have the ability to function as PMO. The purpose of this activity is to carry out PMO training for STO. Yohanes Maria Vianey Naibonat church youth through the method of lectures, discussions and microscopic training. The level of knowledge was measured using a questionnaire in the pre-test and post-test training. Youth who have been trained will be directed to become PMO’s for their families and closest neighbors who suffer from TB as well as agents of change in changing healthy behavior to prevent TB infection. The results of the activity showed a change in the level of knowledge before and after training from72% enough category to be good 89%. It was concluded that empowering church youth as PMO is an effort to suppress the increase in TB cases. The provision of PMO training can increase level of knowledge about TB so that regular and scheduled training will increase the ability and understanding of the role of PMO in reducing the incidence of TB in the community.